Infliximab-induced autoimmune hepatitis. Issue 5 (24th May 2021) - Jenkins, Alexander; Austin, Amy; Hughes, Kathryn; Sadowski, Brett; Torres, Dawn
Abstract : Autoimmune hepatitis (AIH) is an inflammatory disorder of the liver with a wide spectrum of disease presentation, from asymptomatic elevations in liver-associated enzymes to acute liver failure. AIH is classically associated with elevated immunoglobulins and autoantibodies, although approximately 20% of patients with features of AIH lack circulating antibodies. Recently, tumour necrosis factor alpha inhibitors have been implicated in several cases of drug-induced AIH which impact treatment regimens for patients with inflammatory bowel disease (IBD). We present a case of infliximab-induced seronegative AIH responding to budesonide therapy with successful alteration of IBD treatment regimen to vedolizumab.